PENGALAMAN GURU DALAM MERANCANG ASESMEN LITERASI TRANSISI PAUD-SD DI SEKOLAH DASAR - Sekar Anggraini; Hendra Budiono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the experiences of elementary school teachers in designing literacy assessments during the transition from Early Childhood Education (PAUD) to Elementary School (SD). The study used a qualitative approach with phenomenological methods. The research subjects consisted of one first-grade teacher and one principal at SD Negeri 55/I Sridadi. Data were collected through in-depth interview s and observations. The results showed that teachers understood literacy assessments not only as a tool to measure reading and writing skills, but also as a means to identify students' learning readiness during the transition. In designing the assessments, teachers attempted to adapt the instruments to the children's characteristics, use simple media, and integrate the assessments into play activities. The main obstacles faced were time constraints, differences in student abilities, and a lack of appropriate assessment guidelines. Nevertheless, teachers demonstrated high levels of creativity and reflection to ensure the assessments remained effective. This study has important implications for improving teachers' capacity in designing adaptive and sustainable literacy assessments in the early grades of elementary school.